Convergent and external validity of risk preference elicitation methods: Evidence from Viet Nam - Trang Thu Vu; Alistair Munro (Asian Development Bank Institute (ADBI), 2024)
In this study, we add to the body of evidence on the reliability of risk preference measurements using evidence from a survey and experiment in rural Viet Nam. We conducted a field survey and experiment with a random sample of 350 households. Subjects face various incentivized elicitation methods, including multiple price lists and Gneezy-Potters-style tasks as well as non-incentivized tasks and general attitude questions about willingness to take on risk. Most elicitation methods provide evidence that respondents are, on average, risk-averse. Respondents appear less risk-averse in the self-assessment method than with other methods. Therefore, comparing risk preferences elicited from the survey and experiments should be done with caution. Unlike other studies on supporting the use of self-assessment of risk attitude in surveys such as Dohmen et al. (2011), we find that self-assessment, both in general and in specific contexts, has limited validity as it has the smallest or no relation with other measures. This finding could reflect the differences between developed and developing countries. Lastly, the multiple price list and loss-gain measures are stronger at predicting behaviors in experiments and predicting risky behaviors than other elicitation measures.
Keywords: D90; O10; 330; risk preferences; experiment; validity